New possibilities for the gauging of chiral bosons - Abreu, EMC; Dutra, Alvaro de Souza [UNESP]; Wotzasek, C. (American Physical Soc, 2003)
We study a new mechanism for the electromagnetic gauging of chiral bosons showing that new possibilities emerge for the interacting theory of chiral scalars. We introduce a chirally coupled gauge field necessary to mod out the degree of freedom that obstructs gauge invariance in a system of two opposite chiral bosons soldering them together.